2020
DOI: 10.1590/s1678-9946202062013
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of antiviral therapy during the second or the third trimester for preventing mother-to-child hepatitis B virus transmission: a systematic review and meta-analysis

Abstract: This is an open-access article distributed under the terms of the Creative Commons Attribution License.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Postponement of treatment to a point later than 32 weeks of gestation may result in an insufficient duration of treatment and suboptimal viral load reduction at delivery. 10,20 Guidelines from the American Association for the Study of Liver Diseases and the Asian Pacific Association for the Study of the Liver recommend initiation of treatment at 28 to 32 weeks of gestation. 9,21 The present study demonstrated a feasible framework for triage of nearly all pregnant women with high viral loads before their dates of delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Postponement of treatment to a point later than 32 weeks of gestation may result in an insufficient duration of treatment and suboptimal viral load reduction at delivery. 10,20 Guidelines from the American Association for the Study of Liver Diseases and the Asian Pacific Association for the Study of the Liver recommend initiation of treatment at 28 to 32 weeks of gestation. 9,21 The present study demonstrated a feasible framework for triage of nearly all pregnant women with high viral loads before their dates of delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have emerged in recent years that favor the use of tenofovir disoproxil fumarate (TDF) because of its high efficacy and safety profile in addition to its high barrier to resistance (Table 4). [6][7][8][9][10][11][12] Patients who become pregnant while already maintained on HBV treatment should be assessed for both the appropriateness of the drug therapy and their response to treatment. Patients should be continued on HBV antiviral therapy (AVT) throughout the pregnancy and after delivery in the long term.…”
Section: Hepatitis B Virusmentioning
confidence: 99%